Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, dan Kecerdasan Spiritual Terhadap Hasil Belajar IPA Siswa SMP Negeri di Kabupaten Sinjai - Muzdalifah Muzdalifah; Muhammad Jufri; Andi Mu’nisa; Yusminah Hala; Rosdiana Ngitung (Universitas Negeri Makassar, 2018)
The objectives of the research are to discover (i) the influence of Intellectual intelligence on Natural Science learning result, (ii) the influence of Emotional intelligence on Natural Science learning, (iii) the influence of Spiritual intelligence on Natural Science learning result, and the influence of intellectual, emotional, and spiritual intelligence simultaneously on Natural Science learning result . The data collection technique used was questionnaire of intellectual, emotional, and spiritual intelligences. The result of the research reveal that (i) most of students’ intellectual intelligences is in very high category, most of students’ emotional intelligences is in medium category and the most of the students’ spiritual intelligences in high category, (ii) there is positive and significant influence of the students’ intellectual intelligences on the students’ learning results. The intellectual intelligences has strong influence on the students’ learning results, (iii) there is positive and significant influence of the students’ emotional intelligences on the students’ learning results. The emotional intelligences has strong influence on the students’ learning results, and (iv) there is positive and significant influence of intellectual, emotional, spiritual intelligence simultaneously of the students’ learning results. The intellectual, emotional, spiritual intelligence have fairly strong influence on the students’ learning results.